2020
DOI: 10.1523/jneurosci.0769-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

CCKergic Tufted Cells Differentially Drive Two Anatomically Segregated Inhibitory Circuits in the Mouse Olfactory Bulb

Abstract: Delineation of functional synaptic connections is fundamental to understanding sensory processing. Olfactory signals are synaptically processed initially in the olfactory bulb (OB) where neural circuits are formed among inhibitory interneurons and the output neurons mitral cells (MCs) and tufted cells (TCs). TCs function in parallel with but differently from MCs and are further classified into multiple subpopulations based on their anatomic and functional heterogeneities. Here, we combined optogenetics with el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 97 publications
(159 reference statements)
10
39
0
Order By: Relevance
“…Mitral cells and sTCs have distinct odorant response properties ( Fukunaga et al, 2012 ; Igarashi et al, 2012 ). Many sTCs express the peptide neurotransmitter cholecystokinin (CCK; Seroogy et al, 1985 ), these neurons are strongly driven by monosynaptic input from OSNs ( Sun et al, 2020 ), and we have previously shown that they have faster-onset and less diverse odorant-evoked responses than the general MT cell population ( Economo et al, 2016 ; Short and Wachowiak, 2019 ; Eiting and Wachowiak, 2020 ). We compared glutamate dynamics onto CCK + sTCs and piriform cortex-projecting MT cells (pcMTs), using Flex.AAV9.iGluSnFR.A184S virus injection into the superficial EPL of CCK-IRES-Cre mice or retrograde viral expression via injection into anterior piriform cortex of Tbet-Cre mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mitral cells and sTCs have distinct odorant response properties ( Fukunaga et al, 2012 ; Igarashi et al, 2012 ). Many sTCs express the peptide neurotransmitter cholecystokinin (CCK; Seroogy et al, 1985 ), these neurons are strongly driven by monosynaptic input from OSNs ( Sun et al, 2020 ), and we have previously shown that they have faster-onset and less diverse odorant-evoked responses than the general MT cell population ( Economo et al, 2016 ; Short and Wachowiak, 2019 ; Eiting and Wachowiak, 2020 ). We compared glutamate dynamics onto CCK + sTCs and piriform cortex-projecting MT cells (pcMTs), using Flex.AAV9.iGluSnFR.A184S virus injection into the superficial EPL of CCK-IRES-Cre mice or retrograde viral expression via injection into anterior piriform cortex of Tbet-Cre mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mitral cells and superficial tufted cells (sTCs) have distinct odorant response properties 26,27 . Many sTCs express the peptide neurotransmitter cholecystokinin (CCK) 28 ; these neurons are strongly driven by monosynaptic input from OSNs 29 , and we have previously shown that they have faster-onset and less diverse odorant-evoked responses than the general MT cell population 6,24,30 . We compared glutamate dynamics onto CCK+ sTCs and piriform cortex-projecting MT cells (pcMTs), using Flex.AAV9.iGluSnFR.A184S virus injection into the superficial EPL of CCK-IRES-Cre mice or retrograde viral expression via injection into anterior piriform cortex of Tbet-Cre mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sensory-evoked glutamatergic input onto MT cells can arise from OSNs or from multisynaptic excitation involving dendritic glutamate release from ET cells and, possibly, sTCs 16,29,41-43 . In addition, inhibitory circuits can modulate multisynaptic glutamate signaling 11,12,17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For OB projection neurons, however, only little information about chemotypes is available at this point: Pcdh1 and Tbx21 (Haddad et al, 2013; Nagai et al, 2005) have been shown to be selectively expressed in a subset of OB projection neurons. CCK distinguishes a subset of TCs (superficial TCs, (Liu and Shipley, 1994; Seroogy et al, 1985; Short and Wachowiak, 2019; Sun et al, 2020). Vasopressin expressing cells might constitute a further subset of superficial TCs (Lukas et al, 2019), and recently the Lbhd2 gene has been used to obtain more specific genetic access to MCs (Koldaeva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%